Complications following cranioplasty and relationship to timing: A systematic review and meta-analysis. (November 2016) - Malcolm, James G.; Rindler, Rima S.; Chu, Jason K.; Grossberg, Jonathan A.; Pradilla, Gustavo; Ahmad, Faiz U.
Highlights: The timing of delayed cranioplasty and complications were cataloged among published studies. Early cranioplasty (<3 months) is associated with increased odds of hydrocephalus. Early cranioplasty after trauma is associated with reduced odds of extra-axial fluid collections. There was no significant difference among any other complication, including infection. Abstract: The optimal timing of cranioplasty after decompressive craniectomy has not been well established. The purpose of this study was to evaluate the relationship between timing of cranioplasty and related complications. A systematic search of MEDLINE, Scopus, and the Cochrane databases was performed using PRISMA guidelines for English-language articles published between 1990 and 2015. Case series, case–control and cohort studies, and clinical trials reporting timing and complication data for cranioplasty after decompressive craniectomy in adults were included. Extracted data included overall complications, infections, reoperations, intracranial hemorrhage, extra-axial fluid collections, hydrocephalus, seizures, and bone resorption for cranioplasty performed within (early) and beyond (late) 90 days. Twenty-five of 321 articles met inclusion criteria for a total of 3126 patients (1421 early vs. 1705 late). All were retrospective observational studies. Early cranioplasty had significantly higher odds of hydrocephalus than late cranioplasty (Odds Ratio [OR] 2.38, 95% Confidence Interval [CI] 1.25–4.52, p  = 0.008). There was no difference in odds of overall complications, infections, reoperations, intracranial hemorrhage, extra-axial fluid collections, seizures, or bone resorption. Subgroup analysis of trauma patients revealed a decreased odds of extra-axial fluid collection (OR 0.30, p  = 0.02) and an increased odds of hydrocephalus (OR 4.99, p  = 0.05). Early cranioplasty within 90 days after decompressive craniectomy is associated with an increased odds of hydrocephalus than with later cranioplasty, but no difference in odds of developing other complications. Earlier cranioplasty in the trauma population is associated with fewer extra-axial fluid collections.